PRODUKSI KARKAS DAN NON KARKAS PADA BROILER YANG DIBERI PAKAN LIMBAH SAYUR DENGAN PROPORSI YANG BEDA - Jun, Frumensia Rofina Fioni; Supartini, Nonok; Sumarno, Sumarno; Astuti, Farida Kusuma; Nurul, Mohammad (BUANA SAINS, 2024)
The purpose of this research was to find out how the effect of vegetable waste on the quality of carcasses and non-carcasses of broiler chickens. The research used a Complete Randomized Design (RAL) with five treatments and five tests. P0 (control of feed without vegetable waste), P1 (use of 5% vegetable waste in 100% of feed formulations), P2 (use of 10% of vegetable waste in 100% of feed formulations), P3 (use of 15% of vegetable waste in 100% of feed formulations), and P4 (use of 20% of vegetable waste in 100% of feed formulations) are the difference in the percentage of vegetable waste used in the study. The parameters observed the quality of carcasses and non-carcasses of broiler chickens. The results showed that the use of vegetable waste in broiler chicken feed did not have a significant effect on non-carcass weight but had a real impact on carcass weight. The results showed that the variable weight of broiler carcasses, especially treatment with 15% vegetable waste formulations, gave the best results